2021
DOI: 10.3390/plants10061071
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Plant Growth-Promoting Metabolites by Phosphate-Solubilizing Bacteria in Maize Rhizosphere

Abstract: Microbial treatment has recently been attracting attention as a sustainable agricultural strategy addressing the current problems caused by unreasonable agricultural practices. However, the mechanism through which microbial inoculants promote plant growth is not well understood. In this study, two phosphate-solubilizing bacteria (PSB) were screened, and their growth-promoting abilities were explored. At day 7 (D7), the lengths of the root and sprout with three microbial treatments, M16, M44, and the combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 78 publications
2
9
0
Order By: Relevance
“…From data illustrated in Table ( 7), the total amino acids were differed by the isolate's differences, and our results closer to the data obtained from Ibáñez et al, (2021) PSB had a favorable impact on barley development, resulting in an increase in metabolic activity of several active chemicals., PGPR traits tested in vitro are generally associated with the ability of beneficial bacteria to promote plant growth and health was increased according to siderophore and HCN production. Because of their active participation in various processes of plant growth and development, Shen et al, (2021), demonstrated that amino acids were the focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From data illustrated in Table ( 7), the total amino acids were differed by the isolate's differences, and our results closer to the data obtained from Ibáñez et al, (2021) PSB had a favorable impact on barley development, resulting in an increase in metabolic activity of several active chemicals., PGPR traits tested in vitro are generally associated with the ability of beneficial bacteria to promote plant growth and health was increased according to siderophore and HCN production. Because of their active participation in various processes of plant growth and development, Shen et al, (2021), demonstrated that amino acids were the focus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of PGPR candidates may be hired as eco-friendly biofertilizers and biocontrol agents in organic farming (Utama et al, 2021). Shen et al, (2021) were investigated those amino acids and their derivatives were better to understand the metabolomic mechanism of microbial inoculants on plant growth-promoting effects.…”
mentioning
confidence: 99%
“…The study revealed the redirection of amino acids towards energy production, feeding into the tricarboxylic acid (TCA) cycle and protein biosynthesis for increased plant biomass and, thus, growth promotion. The UHPLC-MS/MS profiling of plant growth-promoting metabolites in the rhizosphere of maize plants showed the differential accumulation of amino acids, amino acid derivatives, and other different metabolic compositions, resulting in improved root and shoot length [ 64 ]. This study used PLS-DA to determine and select significant differential metabolites (potential metabolic markers) matched against the KEGG database for further investigation.…”
Section: Current Applications Of Plant Metabolomics In Crop Improvementmentioning
confidence: 99%
“…As expected, the reaction depended on the plant species used due to the following differences: (i) The effect of the applied compound, and (ii) the type of response. The authors explained this variation by differences in both the uptake of the tested compounds and metabolic activity of the tested plant species [203,204]. This latter explanation implies species specific differences in metabolism (Figure 5).…”
Section: Response Of Plants To Environmental Stress In Dependence Of ...mentioning
confidence: 99%